APPLICATION OF SCIENTIFIC APPROACH TO IMPROVE THE RESULTS OF ENGLISH STUDENTS IN X IPA-1 GRADE AT SMAN 1 MARON - Cicis Wediastriana (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2020)
The purpose of this study is  find out the Application of Scientific Approach   Improve the Student Learning Outcomes of the    English Subjects for  Congratulations and Praise to X IPA -1   Grade at  SMA NEGERI 1  in Academic Yearat    2019/ 2020 This study uses an action research as much as two cycles. Each round consists of four stages namely action planning, action implementation, action observation, reflection and action refission. The target of this research is the Students of  X-IPA 1 Grade of SMAN I Maron in Academic Year 2019/2020. The data obtained in the form of formative test results, observation sheets of teaching and learning activities, student achievement has increased from cycle 1 to cycle 2. The conclusion of this research is the Use of Scientific Approach can improve the student learning outcomes of  X-IPA 1 Grade  of SMAN I Maron  in   Academic Year 2019/2020 . It was found that classical completeness in the first cycle was (66.7%) and in the second cycle (93.3%) from the analysis.